2014
DOI: 10.1158/0008-5472.can-14-0093
|View full text |Cite
|
Sign up to set email alerts
|

IL4 Receptor ILR4α Regulates Metastatic Colonization by Mammary Tumors through Multiple Signaling Pathways

Abstract: Interleukin-4 (IL4), a cytokine produced mainly by immune cells, may promote the growth of epithelial tumors by mediating increased proliferation and survival. Here, we show that the type II IL4 Receptor (IL4R) is expressed and activated in human breast cancer and mouse models of breast cancer. In metastatic mouse breast cancer cells, RNAi-mediated silencing of IL4Rα, a component of the IL4 receptor, was sufficient to attenuate growth at metastatic sites. Similar results were obtained with control tumor cells … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
80
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 34 publications
11
80
1
Order By: Relevance
“…Using IL4 knockout mice, we also showed that IL4 ligand drives enhanced lung metastatic tumor growth. 6 However, our finding that IL4 knockout mice injected with IL4Ra K D cells had a greater reduction in tumor burden than either IL4 knockout or IL4Ra K D alone could implicate a role for IL13 in vivo. IL4 is the prototypical ligand for the IL4 receptor.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Using IL4 knockout mice, we also showed that IL4 ligand drives enhanced lung metastatic tumor growth. 6 However, our finding that IL4 knockout mice injected with IL4Ra K D cells had a greater reduction in tumor burden than either IL4 knockout or IL4Ra K D alone could implicate a role for IL13 in vivo. IL4 is the prototypical ligand for the IL4 receptor.…”
mentioning
confidence: 65%
“…In addition, we also saw a reduction in pAkt serine 473 and pErk levels in IL4Ra K D lung metastases compared to control, confirming the relevance of IL4/IL4Ra-activated pAkt and pErk in vivo. 6 In summation, we have identified IL4/IL4R signaling as a potent driver of mammary cancer metastasis. Approximately 80% of cancers are epithelial in origin.…”
mentioning
confidence: 94%
“…Although the activation of IL4/STAT6 signal boosts both the tumorigenic and metastatic activity of breast cancer cells, its loss exerts an antitumor activity through the activation of CD8 þ T cells, in a CD4 þ L Th cell-independent manner (19,48). Although the role of T h2 cytokines in cancer is still contradictory and context dependent (49), we here demonstrated that targeting IL4 pathway fostered the cytotoxicity of CD8 þ T cells, by increasing intracellular IFNg content and decreasing their PD-1 expression, expression that is related with a shorter overall survival in epithelial-originated cancer patients (50).…”
Section: Discussionmentioning
confidence: 99%
“…However, insufficient data are available on the mechanisms regulating this phenomenon. Recently, it has been demonstrated that, in a syngeneic breast cancer mouse model, the IL4/ IL4R interaction promotes metastatic spreading by activating the MAPK pathway (19).…”
Section: Introductionmentioning
confidence: 99%
“…She recently used a novel three-dimensional co-culture system to investigate mechanisms leading to release of dormancy in the bone marrow microenvironment, and found evidence that inflammatory cytokines involved in bone repair and turnover can activate latent disseminated breast cancer cells [8]. CEM Board Member Barbara Fingleton investigates how MMPs and the Th2 cytokines IL4 and IL13 and their receptors regulate malignant progression of breast and colon cancers [9,10]. Her recent review on IL4/IL4R as a target for metastasis disease provides a valuable resource for colleagues in the field [11].…”
mentioning
confidence: 99%